Significados dos problemas mentais na infância: quem olha? O que se olha? Como se olha? - Esper, Marcos Venicio [UNIFESP] (2016)
This essay addressed the different discourses of professionals in family health strategy (FHS) to analyze and reflect about the meanings of mental health problems in childhood, highlighting who sees it, what is seen and how they look to these problems, starting at the Ethnographic research in the city of Passos - MG. Taking as a reference the theoretical and methodological concepts of culture and meanings, closely linked, the qualitative research, based on the ethnography, allowed the approach and understanding of particular experiences related to mental problems in childhood. There is a consensus among the professionals that the topic is relevant, although the professionals feels unprepared to act with the population of children with mental problems. The routine of the professionals is full of situations requiring close observation of the context, always aiming the decision complex-making process technique. It was verified that the directional attention of the professionals to the children with mental problems, was built with base of daily experiences, however, with some variations. Along this search, it was noticed the family and school participation in the child life, although it was revealed by itself as inequalities between the "who" and "how" care the child. Through the speeches of professionals, they observed a difference between the daily practice facing a child with mental problems and what think about the topic. In the deciding, which way a child will walk in treatment is imperative and essential the engagement between the team of professionals and the study of each case in its specificity, without generalizations. It is required new studies, which address the issue of mental health in childhood, providing an overview of the existing scientific production. It is expected through this work, to provoke new further discussions and new perspectives about the importance of the theme in national studies.